Inhibition of CtBP1 activity by Akt-mediated phosphorylation - Merrill, Jacqueline C. (2010)
Pc2 (Cbx4) is a member of the chromobox family of polycomb proteins, and is a SUMO E3 ligase for the transcriptional corepressor, CtBP1. Here we show that both CtBP1 and Pc2 are phosphorylated by the kinase Akt1, which is activated by growth factor signaling via the PI3-kinase pathway. In the presence of Pc2, phosphorylation of CtBP1 is increased, and this requires interaction of both CtBP1 and Akt1 with Pc2. Pc2 promotes CtBP1 phosphorylation by recruiting Akt1, and in part by preventing de-phosphorylation of activated Akt1. Alteration of the Akt-phosphorylated residue in CtBP1 to a phosphomimetic results in decreased CtBP1 dimerization, but does not prevent interaction with other transcriptional regulators. The phosphomimetic mutant of CtBP1 is expressed at a lower level than the wild type protein, resulting in decreased transcriptional repression. We show that this CtBP1 mutant is targeted for poly-ubiquitylation and is less stable than the wild type protein. Coexpression of Pc2 and Akt1 together results in both phosphorylation and ubiquitylation of CtBP1, thereby targeting CtBP1 for degradation. This work suggests that Pc2 may coordinate multiple enzymatic activities to regulate CtBP1 function.